2010
DOI: 10.1002/ijc.25436
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of neuroblastoma outcome based on miRNA expression profiles

Abstract: For neuroblastoma, the most common extracranial tumour of childhood, identification of new biomarkers and potential therapeutic targets is mandatory to improve risk stratification and survival rates. MicroRNAs are deregulated in most cancers, including neuroblastoma. In this study, we analysed 430 miRNAs in 69 neuroblastomas by stem-loop RT-qPCR. Prediction of event-free survival (EFS) with support vector machines (SVM) and actual survival times with Cox regression-based models (CASPAR) were highly accurate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 41 publications
(71 reference statements)
2
82
0
2
Order By: Relevance
“…Other studies have confirmed direct binding of N-myc to the mir-17-92 promoter (50, 55), as well as a positive correlation between expression of MYCN and members of the mir-17-92 cluster in primary tumors and/or neuroblastoma cell lines (49,51,(55)(56)(57)(58)(59)(60)(61). As miRNAs simultaneously target a variety of different mRNAs, it became clear that activation of the mir-17-92 cluster enables N-myc to turn multiple cellular processes toward malignant transformation.…”
Section: N-myc Induces Mirna Expressionmentioning
confidence: 68%
See 3 more Smart Citations
“…Other studies have confirmed direct binding of N-myc to the mir-17-92 promoter (50, 55), as well as a positive correlation between expression of MYCN and members of the mir-17-92 cluster in primary tumors and/or neuroblastoma cell lines (49,51,(55)(56)(57)(58)(59)(60)(61). As miRNAs simultaneously target a variety of different mRNAs, it became clear that activation of the mir-17-92 cluster enables N-myc to turn multiple cellular processes toward malignant transformation.…”
Section: N-myc Induces Mirna Expressionmentioning
confidence: 68%
“…Expression of mir-542-5p was nonrandomly distributed among tumor genetic subtypes, with lowest expression in MYCN-amplified tumors (77% completely lacking expression) and highest expression in stage 1,2,3 and 4S tumors (24% lacking mir-542-5p). Patients with tumors lacking mir-542-5p expression had the poorest prognosis independently of the MYCN status in the tumors (60,75). Bray and colleagues further showed that mir-542-5p overexpression in MYCN-amplified and nonamplified neuroblastoma cells reduced invasiveness in vitro, and restricted tumor growth and metastasis in vivo when cells were orthotopically injected into CB-17/SCID mice.…”
Section: N-myc-regulated Tumor Suppressor Mirnas In Neuroblastomamentioning
confidence: 98%
See 2 more Smart Citations
“…All these results prompted the introduction of RA and its derivatives into therapeutic protocols for neuroblastoma patients, with some success especially in the treatment of minimal residual disease (24 -26). Although several evidences support a role for miRNAs in neuroblastoma pathogenesis (27)(28)(29)(30) and the usefulness of miRNA profiles for neuroblastoma diagnostics, classification, and prognosis has been recently reported (31)(32)(33), little is known about the involvement of miRNAs in RA-induced differentiation of neuroblastoma cells.…”
Section: Micrornas (Mirnas Mirs)mentioning
confidence: 99%